2020
DOI: 10.1101/2020.01.29.924399
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of the cingulate cortex in the generation of motor tics and the experience of the premonitory urge-to-tic in Tourette syndrome

Abstract: Tourette syndrome (TS) is a neurological disorder of childhood onset that is characterised by the occurrence of motor and vocal tics. TS is associated with cortical-striatal-thalamic-cortical circuit [CSTC] dysfunction and hyper-excitability of cortical limbic and motor regions that are thought to lead to the occurrence of tics.Individuals with TS often report that their tics are preceded by 'premonitory sensory/urge phenomena' (PU) that are described as uncomfortable bodily sensations that precede the executi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…A study using both VBM and structural covariance network mapping focused on this region. 60 This study found, first, decreased GM volume within the ACC and, second, increased structural covariance between the ACC and the motor parts of the cerebellum, the inferior frontal cortex and the posterior cingulate cortex.…”
Section: Neuroimaging Studiesmentioning
confidence: 48%
“…A study using both VBM and structural covariance network mapping focused on this region. 60 This study found, first, decreased GM volume within the ACC and, second, increased structural covariance between the ACC and the motor parts of the cerebellum, the inferior frontal cortex and the posterior cingulate cortex.…”
Section: Neuroimaging Studiesmentioning
confidence: 48%
“…However, in the current study, these clinical subgroups (among subjects whose comorbid symptom records were available) did not differ in terms of hippocampal volume. Alternatively, the nonsignificant group difference may be due to variance with age: although Peterson et al found greater hippocampal volume in children, some subregions became smaller than in controls by adulthood [16], and reduced hippocampal volumes have been reported in adolescents [44]and in TS adults with co-morbid OCD [19]. On the other hand, the data collected using the prospective motion correction MR sequence, and with tics carefully screened by face-to-face interview, video recording of the child sitting alone, and a semi-standardized diagnostic interview (K-SADS), revealed increased hippocampal volumes in the NewTics and TS groups compared to the Tic-free group.…”
Section: Discussionmentioning
confidence: 99%